2010
DOI: 10.1007/82_2010_15
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Models to Study Varicella-Zoster Virus Infection of Neurons

Abstract: Varicella zoster virus (VZV) infection results in the establishment of latency in human sensory neurons. Reactivation of VZV leads to herpes zoster which can be followed by persistent neuropathic pain, termed post-herpetic neuralgia (PHN). Humans are the only natural host for VZV, and the strict species specificity of the virus has restricted the development of an animal model of infection which mimics all phases of disease. In order to elucidate the mechanisms which control the establishment of latency and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 84 publications
0
11
0
Order By: Relevance
“…Thus, VZV gene silencing in neurons is a cell type-specific characteristic of the VZV–host interaction. Infection of explanted foetal DRG neurons in vitro showed that IE63 has anti-apoptotic functions that might facilitate this transition 88,89 .…”
Section: Neurotropismmentioning
confidence: 99%
“…Thus, VZV gene silencing in neurons is a cell type-specific characteristic of the VZV–host interaction. Infection of explanted foetal DRG neurons in vitro showed that IE63 has anti-apoptotic functions that might facilitate this transition 88,89 .…”
Section: Neurotropismmentioning
confidence: 99%
“…The model also revealed roles for innate responses in virus control in skin (Ku et al 2005). SCID-hu mice with human ganglionic/neurological tissue (Zerboni et al 2010a), coupled with ex vivo culture models such as human fetal ganglia explants and model neuronal cultures (Christensen et al 2011; Gowrishankar et al 2007; Steain et al 2010; Markus et al 2011; Pugazhenthi et al 2011), will likely shed light on aspects of the VZV latent state and VZV neurotropism. However, the assessment of pain is a conscious response that requires functioning in vivo models with intact sensory enervation of both peripheral and central systems.…”
Section: The Rodent Model Of Vzv-induced Painmentioning
confidence: 99%
“…Neuronal infection becomes persistent through the establishment of latency, and subsequent reactivation usually leads to anterograde axonal transport to the periphery and the formation of lesions typical of herpes zoster (shingles), usually in older or immunocompromised persons. Unlike the related alphaherpesviruses pseudorabies virus (PrV) and herpes simplex viruses (HSV) whose wider host range has facilitated study in animal systems, VZV is highly human-tropic: infection of most animal neurons does not result to a full productive infection (Steain et al 2010). There have been a few studies of VZV infection of isolated human fetal dorsal root ganglion (DRG) neurons; however, the limited accessibility to this material has resulted in the direct demonstration of axonal transport and retrograde infection of neurons by VZV being performed only very recently by our groups (Markus et al 2011).…”
Section: Introductionmentioning
confidence: 99%